PRACTICAL TRAINING BASED ON ROBOTICS FOR FUTURE SUPPLY CHAIN SPECIALISTS - Gulnora, Buronova; Mekhrangiz, Halimova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the role of robotics in logistics education by developing a practice-oriented training model that equips students with the technical and professional competencies required for future supply chain environments, addressing the increasing digitalization of logistics processes and the demand for automation. Method: A practice-driven design was applied to create a robotics-assisted learning framework for logistics students, incorporating warehouse robotics, simulation tools, and interactive platforms that support hands-on activities, with data collected through student performance assessments, structured observations, and surveys, while emphasizing experiential learning, problem-solving exercises, and teamwork activities aligned with real-world logistics operations. Result: Findings show that students engaged in robotics-based training developed stronger abilities to manage automated workflows, interpret logistics processes, and apply theoretical concepts in practice, while participants demonstrated higher engagement, increased motivation, and improved collaboration compared to traditional lecture-based formats. Novelty: The integration of robotics into logistics education provides a promising pathway for developing supply chain specialists who are adaptable to emerging technologies, fostering both technical skills and critical thinking, and enabling learners to actively contribute to the advancement of smart and efficient supply chain systems. Results: Findings show that students engaged in robotics-based training developed stronger abilities to manage automated workflows, interpret logistics processes, and apply theoretical concepts in practice. Participants demonstrated higher engagement, increased motivation, and improved collaboration compared to traditional lecture-based formats. Conclusion: The integration of robotics into logistics education provides a promising pathway for developing supply chain specialists who are adaptable to emerging technologies. The proposed framework fosters both technical skills and critical thinking, enabling learners to actively contribute to the advancement of smart and efficient supply chain systems.